The Influence of Omnichannel Marketing and Product Assortment on Brand Engagement Mediated by Customer Experience - Arabiy Mahju, Muchammad Ilham Syarifullah; Dewi, Liliana (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study investigates the influence of omnichannel marketing and product assortment on brand engagement, with customer experience as a mediating variable, in the case of Pertamina Lubricants. Design/methodology/approach: Using a quantitative approach, data were collected through surveys from 384 Pertamina Lubricants consumers in Surabaya and analyzed using Partial Least Squares (PLS). Findings: Omnichannel marketing and product assortment have a direct significant impact on brand engagement. Customer experience was found to be the strongest predictor of brand engagement and also mediates the effect of the independent variables on brand engagement. Research limitations/implications: The research is limited to Pertamina Lubricants consumers in Surabaya and may not reflect consumer behavior in different regions or industries. Practical implications: The findings suggest that marketers should enhance cross-channel integration and curate product assortments to enhance customer experience and brand engagement. Originality/value: This study contributes to the literature by integrating omnichannel marketing, product assortment, and customer experience to explain brand engagement. Paper type: Research paper